A 3D architecture composite of porous vanadium nitride nanoribbons and reduced graphene oxide as a high-efficiency counter electrode for dye-sensitized solar cells. Issue 2 (3rd January 2018) - Wang, Guiqiang; Hou, Shuo; Yan, Chao; Zhang, Wei
Abstract : 3D PVNN/RGO composite electrode with hierarchical porosity exhibits superior photovoltaic performance competing with that of the conventional Pt electrode. Abstract : A three-dimensional (3D) porous architecture combining porous vanadium nitride nanoribbons with reduced graphene oxide was prepared through a hydrothermal process and subsequent thermal annealing in an ammonia/argon mixed atmosphere. Then, the obtained 3D porous vanadium nitride nanoribbon/reduced graphene oxide (PVNN/RGO) composite was explored as the counter electrode of dye-sensitized solar cells (DSCs). As evidenced by the electrochemical measurements, the 3D PVNN/RGO composite demonstrates excellent electrocatalytic performance, which is comparable to that of Pt. This can be attributed to the fact that the 3D architecture composite of porous vanadium nitride and reduced graphene oxide can simultaneously provide a favorable electrolyte diffusion channel, a fast electron-transport network, and an abundance of efficient electrocatalytic active sites. By employing such PVNN/RGO composite as the counter electrode, the fabricated DSC can achieve a conversion efficiency of 7.43%, which is comparable to that of the conventional Pt counter electrode (7.74%). Therefore, the 3D PVNN/RGO composite is a promising low-cost alternative to the expensive Pt as a counter electrode in DSCs.